Research on Chaotic Digital Image Encryption Algorithm - Jia, Ye; Yu-fu, Zheng; Zi-wei, Yang (Journal of physics. Conference series, 2019)
In view of the problems of pseudo-randomness, complexity, short period and limited precision of traditional digital image encryption technology, this paper improves the traditional chaotic digital image encryption technology. Firstly, a random sequence is generated from the chaotic map according to the definition, and then the design process is improved according to the encryption algorithm, and finally the simulation experiment is performed. The improved algorithm uses the Henon-mapped chaotic sequence to generate the shuffle control parameters, and replaces the gray value with the improved two-dimensional Logistic map sequence, shuffles the array using the Henon map, and changes the image pixels using the improved two-dimensional Logistic map. Grayscale values, these algorithms are highly secure against exhaustive attacks, statistical attacks, and plain-text attacks. Even if the attacker knows the algorithm, it does not know the parameters of the algorithm and cannot obtain image information. The improved encryption algorithm can increase the key space and improve the security performance of the encryption algorithm. The image viewing effect is also very good, and the time is greatly shortened, which can fully meet the real-time requirements.